The 6th International Congress of CiiEM-Immediate and Future Challenges to Foster One Health - Brito, José; Taveira, Nuno; I. Fernandes, Ana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Proceedings reprint brings together a collection of selected papers presented at the sixth Congress of the Egas Moniz Centre for Interdisciplinary Research, held in Caparica from the 5th to the 7th of July, under the theme "Immediate and future challenges to foster One Health". Researchers and health professionals participated in presentations and discussions on the innovation, sustainability and quality of health systems, digital solutions for a healthy society, the promotion of sustainable and circular management of natural resources, and the security of sustainable food and nutrition systems. More than 400 participants registered for the event, which featured presentations by international speakers and undergraduate and graduate students who had the opportunity to disseminate their research work as an important contribution to their education, namely on how to meet the standards of scientific writing and research papers for publication.